دور التقنيات الرقمية في تثمين نشاط التسويق الفندقي -دراسة حالة مركب الغزال الذهبي بالوادي- - لزهر, براهيمي; بوبكر, جديد; محمد, خضرة (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الدراسة إلى معرفة دور التقنيات الرقمية في تثمين نشاط التسويق السياحي و الفندقي بداية بعرض مفاهيم نظرية حول ماهية التقنيات الرقمية ، ثم مدخل إلى التسويق الفندقي ، و أخيرا آثار التقنيات الرقمية على استراتيجيات عناصر المزيج التسويقي السياحي و الفندقي و اسهاماتها في إعادة هندسة عناصر المزيج التسويقي التقليدية ، و لتحقيق هذه الأهداف اعتمدت دراستنا على المنهج الوصفي في ازالة الغموض على بعض المفاهيم المتعلقة بموضوع الدراسة ، حيث تم تصميم استبيان كأداة لجمع البيانات و توزيعه على عينة الدراسة المتمثلة في موظفي مركب الغزال الذهبي ، و تحليل نتائج الاستبيان بالاعتماد على برنامج التحليل الإحصائي (SPSS). و قد توصلت الدراسة إلى أن التقنيات الرقمية أسهمت بشكل كبير في إعادة هندسة و تطوير عناصر المزيج التسويقي و يتضح ذلك من خلال شكل الخدمة المقدمة للعميل (خدمة الكترونية ،تسعير ديناميكي ، توزيع الكتروني ،ترويج الكتروني ، حجز و دفع الكتروني ...) .This study aims to know the role of digital technologies in evaluating the activity of tourism and hotel marketing, starting with presenting theoretical concepts about what digital technologies are, then an introduction to hotel marketing, and finally the effects of digital technologies on the strategies of the elements of the tourism and hotel marketing mix and their contributions to re-engineering the elements of the mix. traditional catalog, In order to achieve these goals, our study relied on the descriptive approach in removing ambiguity on some concepts related to the subject of the study, where a questionnaire was designed as a tool for data collection and distribution to the study sample represented by the employees of the Golden Deer Boat, and the analysis of the results of the questionnaire based on the statistical analysis program (SPSS) . The study concluded that digital technologies contributed significantly to the re-engineering and development of the elements of the marketing mix, and this is evident through the form of service provided to the customer (electronic service, dynamic pricing, electronic distribution, electronic promotion, electronic reservation and payment ...).
Keywords: تقنيات رقمية ، شبكة الانترنت ، تسويق فندقي ، مزيج التسويق الفندقي.; digital technologies, the Internet, hotel marketing, hotel marketing mix.